The Impact of Political Connections and the Effectiveness of Board of Commissioner and Audit Committees on Audit Fees - Intan Ariningrum; Vera Diyanty (Australasian Accounting, Business and Finance Journal, 2017)
This research aims to investigate the impact of political connection and effectiveness of Board of Commissioner and Audit Committee on audit fees. This research uses samples of Non financial companies listed in Indonesia Stock Exchange for the period 2012-2015. The Result of this study are that political connection can positively influence audit fees because the existence of political connection within the firm can increase firm’s inherent risk that assessed by the auditor and the effectiveness of board of commissioner and audit committee can positively influence audit fees because they want higher audit quality from the auditor.
Keywords: Audit Fees; Political Connections; Effectiveness of Board of Commissioner; Effectiveness of Audit Committee.